Hepatitis B under the eyes of students of the Oral Health Assistant course (Research, Society and Development, 2022)
The objective was to evaluate the knowledge, attitude and behavior of students of the Assistant in Oral Health (ASB) course on Hepatitis B, in relation to the risks of contamination, prevention and conduct in the face of exposure. This is a cross-sectional and descriptive study, conducted at a training institute for ASB, in 2019, in São Paulo-SP, Brazil. A self-administered pre-tested questionnaire was applied on the risks of contamination, prevention and conduct in the face of exposure to the Hepatitis B virus. 90.6% stated that they had already been instructed on hepatitis B, but the etiologic agent unknown to 97.0% of the students. 27.1% cited vaccination as the best method of prevention; 18.6% used condoms and 17.1% used PPE. Regarding immunization, 68.9% were immunized; and of these, 34.9% claimed to have received 3 doses of the vaccine. Among the students who already worked as ASB, 48% said they followed biosafety standards. As for the use of PPE, 68% said they used them, with gloves being the most used (92%). For 46.3%, the risk of contracting Hepatitis B is very high for these professionals. There is inadequate knowledge and sub-awareness of students about Hepatitis B, with regard to biosafety practices and failures in their vaccination schedules. Continuous guidance programs should be provided to all health professionals, so that there is an improvement in this situation.